The Social, Economic and Fiscal Effects of Tax Amnesty the Evidence from Kosovo - Abdurrahmani, Enis; Doğan, Zeki (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
Tax amnesty as a common practice has a very important place in the fiscal literature. Empirical evidence suggests that tax amnesties in the short term can increase collection of tax revenues with very low cost. But on the other side tax amnesties can give quite negative effects over the long term through discouraging regular taxpayers’ from their unequal treatment. In this study we have addressed the effects of tax amnesty in the Republic of Kosovo. Based on the survey research with taxpayers’ and through analyses we have defined the attitudes and behaviours of each type of taxpayers’ regarding the social, economic and fiscal effects of tax amnesty in the country. Based on the participation level of the taxpayers’ judgments regarding the effects of tax amnesties, the results have revealed five main judgments according to their level of importance.